Learning Model Jurisprudential Inquiry to Improve Critical Thinking of MTs N 1 Situbondo Students - Badriyah, Lailatul; Warsono, Warsono; Haidar, Ali (Universitas Malikussaleh, 2020)
The Jurisprudential Inquiry learning model is a learning model in its application facilitating learners to be sensitive to social problems, take a position on the problem, and maintain that position / attitude with relevant and valid arguments so as to improve students' critical thinking skills. Critical thinking in this research refers to five indicators, namely the ability to form conclusions, formulate questions, uncover problems, formulate alternative solutions. The purpose of this study was to determine the effect of Jurisprudential Inquiry learning model on critical thinking skills of MTs N 1 Situbondo students. This study uses experimental research design with the form of Quasi-Experimental Design with the type of pretest posttest control group design. The sample in this study was class VIII G numbering 22 students and VIII H a number of 24 students with purposive sampling sampling technique. The technique of collecting data uses test questions with the description form. The data analysis technique in this study is to use the independent sample t-test. The results of this study indicate that there is a significant influence on the use of the Jurisprudential Inquiry learning model on students' critical thinking with indicators formulating conclusions, formulating questions, expressing problems and providing alternative solutions. The results of the hypothesis test show tcount 3.362 and ttable with a significance level (5%) 0.05, degree of freedom (db) = (n-2) then obtained t(0.05) (44) table = 2.015. The results of tcount>ttable,which shows the results of 3.362> 2.015. As for the significance level of 5% (0.05) has a significance value α> 0.05, i.e. (2-tailed) 0.694> 0.05., it can be concluded that thelearning model is Jurisprudential Inquiry more influential than themodel Problem Solving on the critical thinking ability of students on the material emergence of national organizations and the growing spirit of nationalism.